Erratum. (October 2014) - Unknown
Harvey Goldstein, Daphne Kounali, and Anthony Robinson (2008), "Modelling measurement errors and category misclassifications in multilevel models, " Statistical Modelling, 8(3), 243–261. DOI: 10.1177/1471082X0800800302